Clinical Utility of Different Approaches for Detection of Late Pseudoprogression in Glioblastoma With O-(2-[18F]Fluoroethyl)-L-Tyrosine PET. (September 2019) - Kertels, Olivia; Mihovilovic, Milena I.; Linsenmann, Thomas; Kessler, Almuth F.; Tran-Gia, Johannes; Kircher, Malte; Brumberg, Joachim; Monoranu, Camelia Maria; Samnick, Samuel; Ernestus, Ralf-Ingo; Löhr, Mario; Meyer, Philipp T.; et al.
Abstract : Purpose: PET/CT using O-(2-[ 18 F]fluoroethyl)-L-tyrosine ( 18 F-FET) has proven valuable in differentiating tumor recurrence and progression from therapy-induced changes. This study aimed to investigate the diagnostic performance of several analytic approaches in the setting of suspected late pseudoprogression (PsP) in glioblastoma multiforme (GBM). Methods: Retrospective analysis of tumor recurrence was performed in 36 patients with histopathologically confirmed GBM and suspicion of recurrence/disease progression more than 12 weeks from cessation of irradiation based on MRI and Response Assessment in Neuro-Oncology working group criteria. For differentiation of late PsP from true tumor recurrence, images were analyzed semiquantitatively employing tumor-to-brain ratios using 5 different approaches for tumor and normal brain reference region definition, respectively. Histopathology and/or clinical and imaging follow-up served as reference. Respective areas under the receiver operating characteristic curve were compared. Results: 18 F-FET PET was able to reliably differentiate PsP from true tumor progression with areas under the receiver operating characteristic curve ranging from 0.80 to 0.88 (all P < 0.01). Irrespective of the approach chosen, the classification differences between the applied methods were not significant (all P > 0.05), albeit approaches focusing on voxels with the highest uptake tended to perform superior. Conclusions: Irrespective of the analytical approach, 18 F-FET PET is a robust tool for detection of late PsP with only minor differences between different analytical approaches. However, methodological standardization and harmonization are needed to ensure comparability between different centers. Abstract : Supplemental digital content is available in the text.